PENGARUH PROMOSI ONLINE TERHADAP CUSTOMER SATISFACTION DENGAN REPURCHASE INTENTION PADA TOKO FORY SPORT KARAWANG - Nayla fata Salsabila; Yuanita Melliana Putri; Ajat Sudrajat (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
Football is a game sport that is very popular with the Indonesian people. many also make football a hobby and an aspiration. based on the survey football has a rating of 47.6%. Seeing the great opportunity for the large number of people who love soccer, the ForY sport Karawang store started a business selling soccer equipment. From the many competition for sports equipment stores in Karawang, the ForY sport shop to win the competition, the ForY sport shop must be able to provide special treatment for its consumers. Online promotions carried out by ForY sports stores, namely holding give away, giving discounts, and serving customers well, aims to determine the level of customer satisfaction which will have an impact on repeat purchases. Data collection using a questionnaire with a total of 100 respondents who live in Karawang, have visited and bought at least once at the ForY sport shop, aged at least 17 years using purposive sampling technique. The analysis technique in this study uses SPSS with quantitative analysis methods (validation and reliability tests), verification analysis (t test, F test, coefficient of determination, and descriptive analysis. The results of this study are 1) Online Promotion has a significant effect on customer repurchase intention at ForY Sport stores 2) Customer Satisfaction has a significant effect on customer repurchase intention at ForY Sport stores 3) Online promotions have a significant effect on customer satisfaction in customers at ForY Sport stores. future suggestions for stores It would be nice if the variety of promotions be increased again so that in the future it can be more convincing in the decision of consumers to buy apparel and sport shoes so that consumers are satisfied when shopping at ForY sports stores. Maintain the quality of the product being sold. Make sure the quality of service provided is further improved and pay more attention to the waiting room for consumers so that they feel comfortable.